Developing and assessing radical technological changes: lessons from the PBX industry. (1st January 2002) - Jones, Neil
This paper explores an industry where existing firms successfully adapted to radical technological change. The balance of previous work has suggested that incumbent firms identify, develop, and evaluate radical or nonincremental technological changes less successfully than entrants do. Such work suggests that rather than introducing radical new technologies, incumbents tend to bias decisions towards sustaining existing approaches through incremental technological changes. However, evidence from the PBX industry indicates that certain firms may overcome such tendencies to bias and identifies some of the systems and tools apparently responsible for superior incumbent performance in this industry. The results described here suggest that our existing characterisation of how new technologies are evaluated by firms is incomplete. They also suggest that firms may be able to systematically and successfully evaluate, develop and even generate non-incremental technological changes.